Practical Straits of the Forensic Examination in China - Zhong Zhang (Wolters Kluwer Medknow Publications, 2016)
With the revision of the Criminal Procedural Law of the PRC and the Civil Procedural Law of the PRC in 2012, it has entered a new historical stage of litigation system and made significant progress in forensic examination system in China. However, for a long time, the illegal forensic examinations have been commonly seen in forensic practice, the right to start the forensic examination process only lies with public security and judicial authorities, while the parties only have the limited right to apply for supplementary forensic examination or re-examination. To the problem of experts' refusal to appear in court to testify, the Criminal Procedural Law and the Civil Procedural Law have further improved the expert testimony system, but the situation has not fundamentally changed. To compensate for judges' lack of knowledge of professional issues, the expert advisor system is introduced, but there are no workable rules. Besides, judges depend too much on and accept the expert opinions blindly become a common phenomenon in the proceedings.